التركيب الديناميكي لخصائص منحنى (سرعة- زمن) في بناء النماذج الحركية لمراحل مهارة الضرب الساحق بالكرة الطائرة - شبر, أحمد عبد الامير; الحمزة, بركات عبد (Sulaimani Journal for Humanities, 2018)
The importance of science Biomechanics in the study and analysis phases of skill and creating relationships for some variables through dynamic analysis of the characteristics of the speed-time curve to bring it to the level of perfect technical performance in order to complete a portion of the access sports requirements, the need arises to conduct a study to find out and analyze the dynamic variables of the characteristics curve Speed- time for the stages of the skill of the starting position and the law of equilibrium and stability, and the preparatory and law transitional speed to earn player increasing kinetic energy is transferred from the shape horizontal to vertical and achieve projectiles law when breaking the contact of the player with the ground in the flight phase and then the mechanical motor transport values from the trunk of the arm strike and then into a ball through momentum and conservation Act momentum to the last stages of the performance of the law of free fall under conditions similar to the cases of play, and study aimed to identify the dynamic composition and characteristics of the curve values (speed-time) stages beating overwhelming skill of volleyball, and identify the impact of the dynamic structure of the characteristics curve (speed - time) in the construction of kinetic models for the stages of the beating overwhelming skill of volleyball, and I suppose Find a positive effect of the installation of the dynamic characteristics curve (Speed-time) in the construction of kinetic models for the stages of the beating overwhelming skill of the plane of the ball, and was searching through a dynamic installation is a special type of system dynamic where the equation that the evolution of the system linear equation control while dynamic systems in general do not have a closed solutions model, but it can be dynamic systems linear solution fully, also has a group rich array of sports properties, and can also use linear systems to understand the qualitative behavior systems General dynamic, calculates balance points of the system and approximated as a linear system around each of these points, and that means the study of the stages of the beating overwhelming plane ball skill in accordance with these systems, which is about laws and regulations followed in each stage of performance.